Dampak Intellectual Capital Terhadap Profitabilitas Pada Industri Perbankan - Nia Yuniarsih (BIP's JURNAL BISNIS PERSPEKTIF, 2017)
The objective of this study is to examine the influence of Intellectual Capital to Profitability. This study takes sample from 38 bank at the Indonesia Stock Exchange (IDX), which were published in financial report from 2015-2016. The sample was determined based on the following criteria: (a) issued its financial statement ended 31 December; and (b) reporting earnings ended December 31, 2015 and 31 December 2016. Intellectual Capital were measured by Value Added, Value Added of Capital Employed and Structural Capital Value Added. Profitability was measured by Net Profit Margin. The research hypotheses were tested using single regression. The results of this research show that Intellectual Capital had positive significant influence on profitability.